Ultra-specific nucleic acid testing by target-activated nucleases. (3rd October 2022) - Fu, Jinyu; Li, Junjie; Chen, Jing; Li, Yabei; Liu, Jiajia; Su, Xin; Shi, Shuobo
Abstract: Specific and sensitive detection of nucleic acids is essential to clinical diagnostics and biotechnological applications. Currently, amplification steps are necessary for most detection methods due to the low concentration of nucleic acid targets in real samples. Although amplification renders high sensitivity, poor specificity is prevalent because of the lack of highly accurate precise strategies, resulting in significant false positives and false negatives. Nucleases exhibit high catalytic activity for nucleic acid cleavage which is regulated in a programmable manner. This review focuses on the latest progress in nucleic acid testing methods based on the target-activated nucleases. It summarizes the property of enzymes such as CRISPR/Cas, Argonautes, and some gene-editing irrelevant nucleases, which have been leveraged to create highly specific and sensitive nucleic acid testing tools. We elaborate on recent advances in the field of nuclease-mediated DNA recognition techniques for nucleic acid detection, and discuss its future applications and challenges in molecular diagnostics.